2020
DOI: 10.1002/jrsm.1440
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Web‐based Data Visualization and Analysis Tool for Synthetizing on‐farm Research Networks Data

Abstract: The on-farm research network concept enables a group of farmers to test new agricultural management practices under local conditions with support from local researchers or agronomists. Different on-farm trials based on the same experimental design are conducted over several years and sites to test the effectiveness of different innovative management practices aimed at increasing crop productivity and profitability. As a larger amount of historical trial data are being accumulated, data of all the trials requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…For example, the Making Better Fertiliser Decisions for Cropping (BFDC) Systems in Australia project has made data of thousands of fertilization experiments available through a web‐tool called the BFDC Interrogator (Dowling & Spiers, 2013), where users can explore soil test calibrations across multiple combinations of crops and environmental conditions (Bell et al., 2013; Brennan & Bell, 2013; Watmuff et al., 2013). Similarly, one of the most recent and relevant examples in the United States is the Interactive Summaries of On‐Farm Strip Trials (ISOFAST) (Laurent et al., 2020) and Economic Value of On‐Farm Studies (EVOS) (Iowa Soybean Association, 2022) tools, friendly open‐access web‐interfaces that allow users to browse summaries of on‐farm experiments and simulate economic impact for a wide variety of crop management practices in corn ( Zea mays L.) and soybean in Iowa.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Making Better Fertiliser Decisions for Cropping (BFDC) Systems in Australia project has made data of thousands of fertilization experiments available through a web‐tool called the BFDC Interrogator (Dowling & Spiers, 2013), where users can explore soil test calibrations across multiple combinations of crops and environmental conditions (Bell et al., 2013; Brennan & Bell, 2013; Watmuff et al., 2013). Similarly, one of the most recent and relevant examples in the United States is the Interactive Summaries of On‐Farm Strip Trials (ISOFAST) (Laurent et al., 2020) and Economic Value of On‐Farm Studies (EVOS) (Iowa Soybean Association, 2022) tools, friendly open‐access web‐interfaces that allow users to browse summaries of on‐farm experiments and simulate economic impact for a wide variety of crop management practices in corn ( Zea mays L.) and soybean in Iowa.…”
Section: Discussionmentioning
confidence: 99%
“…The OHSPEIMS provides a simple, fast, free solution for constructing a private, highly customized database management system. Shiny is often used to build interactive Web apps, and more and more apps are being published online to simplify some complex analysis processes and data visualization, such as genomic analysis 23 , proteomic analysis 24 , transcriptome analysis 25 , prediction model 26 , complex model 27 and visualization system for COVID-19 pandemic 27 . Hence, it is entirely possible to build a customized dataset management system using Shiny.…”
Section: Discussionmentioning
confidence: 99%
“…Kandel et al (2016) suggested that although fungicides can increase soybean yield in the apparent absence of disease, only 14% of the trials were economically profitable. A web-application, called ISOFAST, synthetizing data from replicated on-farm trials, provides break-even economic analysis of foliar fungicides on maize and soybean (Laurent et al, 2019(Laurent et al, , 2020a. Of the 19 foliar fungicide products evaluated, only six had a >50% probability of exceeding the break-even cost (considering grain market price and application cost averaged over the last 10 years).…”
Section: Mean Yield Log Ratio Of Soybeanmentioning
confidence: 99%
“…For soybean, data were also unbalanced as 82% of the trials were OFTs. A future investigation could consider accounting for covariables, such as fungicide application timing and maize hybrid, to examine their effects on yield response (Kyveryga et al, 2013;Laurent et al, 2020a). Wise et al, (2019) have shown that yield response to a fungicide is affected by the growth stage of the crop at the time of application.…”
Section: Mean Yield Log Ratio Of Soybeanmentioning
confidence: 99%